Operation of an EV Parking Lot Subject to Capacity-Based Grid Tariffs Offering Demand Response - Pinderud, Jonas Henrik; Hansen, Andreas Fosse; Thorvaldsen, Kasper Emil (International Conference on the European Energy Market (Online), 2024)
This work investigate how electrical vehicle (EV) flexibility in a flexible EV parking lot can reduce cost of operation and peak consumption for an office building, while offering grid services. By participating in an incentive-based demand response program (IBDR), the parking lot shuts off charging when prompted. However, the charging strategy is affected by the notice time of the demand response program prior to activation. An optimization problem describing an aggregated parking lot in an office building is developed, minimizing cost of electricity with a monthly demand charge grid tariff. A receding-horizon (RH)-framework is incorporated to make hourly decisions on EV charging and include the IBDR-signals. The decomposition technique stochastic-dual-dynamic programming is applied to strategically account for the long-term cost of the monthly demand charge, given as input to the RH-framework to represent long-term impact of operation. This framework is analyzed for different notice times prior to IBDR-activation for each workday over a month of operation, investigating the impact of IBDR on daily EV charging. With an IBDR-notice given 12 hours prior to activation, the monthly cost of operation increased by 0.6% compared to base case, by increasing EV charging prior and after activation hour. With a notice given at activation, EV charging can only be delayed, leading to a cost of operation increase by 6.29%, with 7.6% of EV demand not being met during the month. The results showcase the importance of notice times to shift EV charging when offering flexibility services to the grid.